Heath impact of xylene exposure on laboratory workers at a selected healthcare facility in Oman - K .V, Sreejaya; Al Quraini, Maryam (International Journal of Occupational Safety and Health, 2025)
Introduction: Xylene is a commonly used chemical in medical laboratories for various purposes such as treating tissues, dyeing and covering sliding. However, exposure to xylene can pose potetial health risks for laboratory staff and healthcare professionals. In order to mitigate these risks, a research project has been proposed to investigate the impact of xylene on histology staff in healthcare facilities in Muscat. The study aims to provide alternative preventive measures and safety procedures to ensure laboratory technicians’ health and safety. Its primary objective is to assess the potential health impacts of xylene exposure on laboratory and healthcare staff in Oman. Methods: A close-ended and open-ended questionnaire was designed to collect data from 115 histhopatholgy workers achieving a 100% response rate. The data was analyzed in Excel. Results: Findings show that exposure to xylene mostly affects the eyes and nose. 21% of participants reported experiencing muscular problems like weakened muscles, loss of coordination, and impaired grip strength. The results also revealed that the third health issue was related to the skin, as 16% of the respondents experienced some form of skin problem due to exposure to xylene, such as skin irritation, itching, peeling, or burns. Conclusion: Based on the study findings, it is evident that xylene has various negative health effects. Alternative substances instead of xylene, such as d-limonene-based products, olive oil, pine oil, and rose oil, are recommended. These alternatives are environmentally friendly and cost effective, although they may not be as effective as xylene. Therefore, it is essential to implement effective measures that prioritize the well-being of histology staff while working with xylene.